A case of sarcoidosis‐associated pulmonary hypertension masquerading as chronic thromboembolic pulmonary hypertension. (1st April 2018) - Bazmpani, Maria Anna; Arsos, Georgios; Zarogoulidis, Paul; Doumas, Argyrios; Dimitroulas, Theodoros; Sianos, George; Hadjimiltiades, Stavros; Kouskouras, Konstantinos; Mayer, Eckhard; Karvounis, Haralambos; Giannakoulas, George
Abstract : Occlusive vasculopathy due to the development and accumulation of granulomas at the level of intima of large vessels, as well as mediastinal lymph nodes and fibrosing mediastinitis secondary to sarcoidosis, causing extrinsic compression of mediastinal vascular structure are uncommon mechanisms of sarcoidosis‐associated pulmonary hypertension. We present a case of a 62‐year‐old woman with a rare manifestation of sarcoidosis, which was misclassified and treated as chronic thromboembolic pulmonary hypertension for a long period. Fluorine‐18‐fluorodeoxyglucose positron emission tomography played a major role in accessing final diagnosis. Mechanisms that lead to development of pulmonary hypertension, the contribution of novel imaging modalities, and treatment options are discussed.